169k views
2 votes
... I don't understand the concept I think first place so um yea oh and I have an exam tomorrow pls I need help

... I don't understand the concept I think first place so um yea oh and I have an-example-1
User VTGroup
by
6.0k points

1 Answer

6 votes

We know that :

  • (a + b)² = a² + b² + 2ab

  • (√(x))^2 = (x^(1)/(2))^2 = x^(2)/(2) = x

  • (√(a))(√(b)) = √(ab)

Now using above ideas, we can solve the Problem


(√(8) + √(2))^2 = (√(8))^2 + (√(2))^2 + 2(√(8))(√(2))


(√(8) + √(2))^2 = 8 + 2 + 2(√(16)) = 8 + 2 + 2(4) = 10 + 8 = 18

User Denden
by
5.4k points